The effect of Cornus mas extract consumption on bone biomarkers and inflammation in postmenopausal women: A randomized clinical trial. (10th May 2021) - Aryaeian, Naheed; Amiri, Fatemehsadat; Rahideh, Seyedeh Tayebeh; Abolghasemi, Jamileh; Jazayeri, Shima; Gholamrezayi, Afsaneh; Motevalian, Manijeh; Solaymani‐Dodaran, Masoud; Taghizadeh, Mohsen; Heshmati, Elaheh; Rimaz, Shahnaz
Abstract : The drastic decrease in estrogen levels in menopausal women can elevate bone resorption and osteoporosis. Cornus mas extract ( C . mas extract) is a potential candidate for treating menopausal‐related bone complications because of its phytoestrogen and anti‐inflammatory contents. It was an interventional double‐blind placebo‐controlled randomized study. Eighty‐four women aged 45–60 years old were randomly allocated to either the extract group receiving 3 capsules of 300 mg C . mas extract or the placebo group receiving 3 capsules of 300 mg of starch powder per day for 8 weeks. Then, venous blood was used to measure bone‐specific alkaline phosphatase (BAP), osteocalcin (OC), C‐terminal telopeptide (TC) as well as serum levels of PTH and hsCRP. Our results indicated the decrease in alkaline phosphatase, PTH, and as an inflammation biomarker, hsCRP, between two groups at the end of the study. No statistically significant difference was observed in telopeptide C, osteocalcin, and calcium between the placebo and extract groups after 8 weeks of intervention. In conclusion, the results indicate that the C . mas extract supplement of 900 mg/day may decrease levels of BAP, PTH, and hsCRP. However, this intervention had no beneficial effect on OC and TC in healthy postmenopausal women.